PTH-095 Persistently elevated faecal calprotectin in the first 12 months of crohn's diagnosis predicts the need for surgery: a nested case-control study. (17th June 2017) - Pavlidis, P; Cockroft, A; Choong, LM; Ravdas, P; Medcalf, L; Tumova, J; Chatu, S; Spirajaskanthan, R; Kent, A; Chung-Faye, G; Dubois, P; Hayee, BH
Abstract : Introduction: There is still uncertainty about the role of faecal calprotectin (FCAL) as a marker of mucosal healing in inflammatory bowel diseases. Available studies have provided evidence on the prognostic role of FCAL in predicting relapses during a short period of time but there is a lack of data on associating FCAL levels over time to hard clinical endpoints. In this study we test the hypothesis that FCAL monitoring identifies Crohn's disease (CD) patients with persistent intestinal inflammation requiring surgery. Method: From a large IBD cohort of patients currently under follow up at King's College Hospital, we identified all the CD patients who were diagnosed locally and had serial FCAL in the context of their routine care (at routine appointments and during flare-ups). Utilising prospectively kept electronic patient records we identified 20 patients, meeting these monitoring criteria, who required a bowel resection for CD≥12 months after diagnosis (cases) and matched them in a 1:2 ratio with controls based on disease duration. Flares were identified based on the physician assessment and endoscopic or radiological findings. Continuous variables are summarised as medians followed by interquartile range. The Fisher exact test was used to compare categorical variables, the Mann-Whitney test for continuous variables and the ROC curve for diagnostic analysis. Results: Median time to surgery was 9.5 years (8, 11) [control group follow up: 8 (7, 10), p=0.28]. Right hemicolectomy was the commonest procedure (14, 70%) followed by panproctocolectomy (2, 10%), small bowel resection (2, 10%) and stricturoplasty (2, 10%). The two groups did not differ in clinical characteristics or time to initiation of a biologic or immunosuppressants. Flares and hospitalisations were more common in the cases group [ 20 (100%) vs. 23 (56%), p=0.0005 and 19 (95%) vs. 19 (48%) p=0.0002, respectively]. At the time of diagnosis, there was a numerical difference in median FCAL between groups [cases: 652 ug/g (168, 1020) vs. controls: 304 ug/g (120, 750), p=0.2]. One year after the diagnosis the median FCAL (FCAL1) was higher in the cases group [ 549 ug/g (152, 1115) vs. 68 ug/g (26, 184), p=<0.001]. The area under the curve for FCAL1 to predict surgery was 0.83, 95% CI(0.73, 0.95) while a cut off at 600 ug/g provided the highest likelihood ratio [18 (15, 69)]. FCAL levels during monitoring were higher in the cases group (calculated as area under the curve/time: 418 ug/g (184, 647) vs. 161 ug/g (51, 347), p=0.018]. Conclusion: FCAL is a marker of mucosal healing in CD. Frequent monitoring identifies patients with clinically meaningful levels of intestinal inflammation associated with flares, hospitalisations and surgery. Disclosure of Interest: None Declared